The effect of perceived ease of use on behavior intention through perceived enjoyment as an intervening variable on digital payment in the digital era - Jasin, Mochammad (Journal of Industrial Engineering & Management Research, 2022)
This study aims to analyze the effect of perceived ease of use on behavior intention through perceived enjoyment as an intervening variable in digital payment. In this study, the researcher used a sampling model with a non-probability technique. The study uses a purposive sampling technique where the researcher will select members of the population who have certain criteria, namely being an e-wallet application user at least 4x in the last two months and a minimum top up of 50,000 IDR Path Analysis can be used in this study to test a hypothesis that indicates the existence of a strong relationship and has an influence between one variable and another variable that has a cause and effect relationship. Partial Least Square (PLS) is one part of SEM and is often used by researchers because it does not require a normal distribution. Respondents in this study were 300 e-wallet users who were determined by simple random sampling. The stages of data analysis test are validity, reliability, termination coefficient and hypothesis testing. The final results obtained in this study indicate that perceived ease of use has a positive influence on behavior intention, perceived ease of use also has a positive influence on perceived enjoyment, Likewise, perceived enjoyment has a positive influence on behavior intention.